Stochastic oil spill modeling for environmental protection at the Port of Taranto (southern Italy). (October 2021) - Liubartseva, S.; Federico, I.; Coppini, G.; Lecci, R.
Abstract: We performed stochastic simulations of hypothetical oil spills from a single-point buoy mooring and subsea pipeline for the Port of Taranto given that this port is an essential strategic hub in the European logistic chain. Our methodology integrates (1) the MEDSLIK-II oil spill model coupled to a high-resolution hydrodynamic model run on an unstructured grid in operational forecasting mode; (2) a hypothetical oil spill scenario based on a historical pipeline rupture at the Port of Genoa, 2016; and (3) randomly sampling the environmental conditions over 2018–2020. The main oil drift was found to be directed southwesterly towards the outlet to the open sea. When oil is transported by highly variable currents, waves and turbulent mixing, it is exposed to multiple strandings and washing-offs from concrete constructions in the port. Consequently, oil tends to be dispersed almost isotropically over the Mar Grande, indicating low to moderate pollution indices. Highlights: Buoy and subsea pipeline as the potential sources of spills at the Taranto Port Stochastic runs of MEDSLIK-II coupled to SANIFS at ultra-fine resolution Southwestern direction dominates in the oil drift First beaching time of 7–17 h determines the timescale of the response. Rating the local sub-regions with respect to the required response urgency